Semantics Of The Childhood Concept - Quiroz, Mariana (MAD, 2024)
The problem of semantics concerns the way in which society is described and, therefore, how the selected is actualized. From the General Theory of Social Systems, the question is approached through the structure/semantics difference. The questions that constitute the research address this relationship, or more precisely, the correspondence (or not) between social evolution and the evolution of ideas. The aim is to answer the questions of in what kind of order and social structures is the concept of childhood produced and stabilized? and, in turn, to what extent do these semantics guide the experiences and expectations of the structures to which they refer? Based on this case, the conditions of possibility of consolidation for a cultivated semantics (concept/word difference) unfold through three structural conditions: the differentiation between psychic systems and social systems, the systemic differentiation of society by functions, and the decoupling between self-reference and binary schemata.